2014
DOI: 10.1159/000365153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daily Consumption of Synbiotic Bread on Insulin Metabolism and Serum High-Sensitivity C-Reactive Protein among Diabetic Patients: A Double-Blind, Randomized, Controlled Clinical Trial

Abstract: Background: This study was conducted to evaluate the effects of daily consumption of synbiotic bread on the metabolic status of patients with type 2 diabetes mellitus. Methods: This randomized, double-blind, controlled clinical trial was performed in 81 diabetic patients. The subjects were randomly assigned to consumption of synbiotic (n = 27), probiotic (n = 27), or control bread (n = 27) for 8 weeks 3 times a day in a 40-gram package. The synbiotic bread contained Lactobacillus sporogenes (1 × 108 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 37 publications
(43 reference statements)
1
67
1
Order By: Relevance
“…The majority of the publications were excluded because they were irrelevant studies, case reports, or reviews. According to the inclusion and exclusion criteria, 15 publications (14 in English and 1 in Chinese) with a total of 902 patients were finally included [12,13,[15][16][17][18][19][20][21][22][23][24][25][26][27]. A flow chart showing the workflow for identifying and screening studies is presented in Fig.…”
Section: Literature Selectionmentioning
confidence: 99%
“…The majority of the publications were excluded because they were irrelevant studies, case reports, or reviews. According to the inclusion and exclusion criteria, 15 publications (14 in English and 1 in Chinese) with a total of 902 patients were finally included [12,13,[15][16][17][18][19][20][21][22][23][24][25][26][27]. A flow chart showing the workflow for identifying and screening studies is presented in Fig.…”
Section: Literature Selectionmentioning
confidence: 99%
“…Tajadadi-Ebrahimi et al showed that the consumption of symbiotic bread for 8 weeks had advantageous effects on insulin metabolism among patients with diabetes [21]. In another double-blind, clinical trial that was done by Akram Kooshki et al about the effect of symbiotics on inflammatory markers on patients with T2DM, has expressed consumption of symbiotic once a day for 8 weeks may decreased serum hs-CRP, IL-6 and TNF-α concentration, which are risk factors for CVD diseases [31].…”
Section: Discussionmentioning
confidence: 99%
“…The good affects of symbiotics on insulin metabolism and inflammatory markers could be interceded by the manufacture of short chain fatty acids, modulation of the intestinal microbiota composition, and reduced expression of inflammation-linked genes. Tajadadi et al showed that the consumption of symbiotic food had advantageous effects on insulin metabolism among patients with diabetes [21]. …”
Section: Introductionmentioning
confidence: 99%
“…The effects of the synbiotic relationship on human health have been addressed in several studies, most aimed at evaluating the effects of synbiotic products on the metabolic status of patients with type 2 diabetes mellitus (DM) (Tajadadi-Ebrahimi et al 2014). Other studies focused on healthrelated quality of life and irritable bowel syndrome symptoms (Šmid et al 2016), weight loss and maintenance in obese patients (Sanchez et al 2014), and glucose metabolism and gut microbiome (Liu et al 2017).…”
Section: Synbiotic Relationship Between Probiotics and Prebioticsmentioning
confidence: 99%